THE REFLECTIVE JOURNEY: INVESTIGATING EFL PRE-SERVICE TEACHERS’ REFLECTIVITY ACROSS MICROTEACHING STAGES - Alfu Nikmah; Rudi Hartono; Issy Yuliasri; Widhiyanto (University of Kuningan, 2026)
Microteaching serves as a practical method in teacher education that helps pre-service teachers develop pedagogical competence through structured teaching practice, reflection, and feedback. This study explores the conduct of pre-service teachers in English as a Foreign Language (EFL) program, and evaluate their teaching practice during microteaching sessions at an Islamic State university in Indonesia. Drawing on Amobi’s (Amobi, 2005) four-stage framework of reflectivity: describing, informing, confronting, and reconstructing. The study explores patterns of reflection emerging from student teachers’ self-reflections and peer evaluations. The participants consisted of 12 sixth-semester undergraduate students (three males and nine females) enrolled in a compulsory microteaching course. Using a qualitative grounded theory approach, data were composed from written self-reflections and peer feedback, and analyzed through content analysis. Findings revealed that participants demonstrated varying levels of reflective engagement across the four stages, showing progress from descriptive awareness of teaching actions to reconstructive insights for future practice. The dominant themes included awareness of teaching design, critical responses to peer feedback, and explicit strategies for improving classroom instruction. The results also indicated that reflective microteaching encouraged professional self-awareness and pedagogical growth among student teachers. The study concludes that reflective teaching practice in microteaching benefits student teachers, lecturers, and institutions by enhancing the quality of teacher preparation and fostering continuous professional development.